Trisomy 18 Syndrome with Incomplete Cantrell Syndrome - Yi-Jen Hou; Fong-Lin Chen; Yan-Yan Ng; Jui-Ming Hu; Suh-Jen Chen; Jia-Yuh Chen; Pen-Hua Su (Elsevier, 2008)
The pentalogy of Cantrell was first described in 1958 by Cantrell and coworkers, who reported five cases in which they described a pentad of findings including a midline supraumbilical thoracoabdominal wall defect, a defect of the lower sternum, abnormalities of the diaphragmatic pericardium and the anterior diaphragm, and congenital cardiac anomalies. Trisomy 18 has an incidence of about 0.3 per 1000 newborns. We present a case of trisomy 18 with incomplete Cantrell syndrome. The patient presented with hypogenesis of the corpus callosum, vermian-cerebellar hypoplasia (Dandy-Walker variant), ventricular septal defect, dextrocardia, patent ductus arteriosus, a defect of the lower sternum, a midline supraumbilical abdominal wall defect with omphalocele, congenital left posterior diaphragmatic hernia (Bochdalek hernia), micrognathia, low-set and malformed ears, rocker-bottom feet, dorsiflexed hallux, hypoplastic nails, short neck, and wrist deformity. Trisomy 18 syndrome was unusually combined with the pentalogy of Cantrell. We present this case because of its rarity and high risk of mortality.